2002
DOI: 10.1002/cncr.10662
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aging on the development of hepatocellular carcinoma in patients with posttransfusion chronic hepatitis C

Abstract: BACKGROUNDHepatitis C virus (HCV) infection is a heterogeneous disease, the natural history of which remains controversial. There is solid evidence that chronic HCV infection is responsible for the occurrence of hepatocellular carcinoma (HCC). The aim of the current cohort study was to determine the rate of the development of HCC from the time of primary HCV infection and to assess the risk factors for the development of HCC in chronic posttransfusion hepatitis C patients.METHODSFour hundred sixty‐nine patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
45
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 37 publications
1
45
0
Order By: Relevance
“…This trend is growing increasingly stronger, and the proportion of death by HCC among all causes of death in patients with cirrhosis and chronic HCV infection has reached 81%. 21 Hamada et al 22 reported that the age of the patient and duration of infection were independent risk factors affecting the development of HCC, and of them, age was the more significant. On average, approximately 30 years pass between the time of transfusion and the time of diagnosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This trend is growing increasingly stronger, and the proportion of death by HCC among all causes of death in patients with cirrhosis and chronic HCV infection has reached 81%. 21 Hamada et al 22 reported that the age of the patient and duration of infection were independent risk factors affecting the development of HCC, and of them, age was the more significant. On average, approximately 30 years pass between the time of transfusion and the time of diagnosis of HCC.…”
Section: Discussionmentioning
confidence: 99%
“…On average, approximately 30 years pass between the time of transfusion and the time of diagnosis of HCC. 1,3,22 According to a nationwide survey in Japan, 23 the mean age at such diagnosis was 63.0 years for males and 66.5 years for females (75% of all patients were anti-HCV-positive). Ninety-two percent of HCC patients were 60 years or older at the time they were diagnosed with HCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, it has been reported that the majority of patients with posttransfusion chronic HCV infection develop HCC after the age of 60 years regardless of when they acquired the HCV infection (10). Moreover, with the increase in fibrosis of transplanted livers in HCV-infected patients, it has been reported that the age of the donor is closely correlated with the rate of progression of fibrosis of the transplanted liver rather than the age of the recipient (11).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, with the increase in fibrosis of transplanted livers in HCV-infected patients, it has been reported that the age of the donor is closely correlated with the rate of progression of fibrosis of the transplanted liver rather than the age of the recipient (11). Namely, the age of the patients who were infected with HCV is a more significant factor than the duration of the HCV infection in regards to the progression of HCV-persistent infection and fibrosis or carcinogenesis (10). Furthermore, in recent years the number of patients in which HCC does not occur before 60 years of age but thereafter develops in patients in their 70s or 80s has been increasing (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%